Nilai-nilai Universalitas Dakwah dalam al-Quran - Abd. Wahid (Islamica: Jurnal Studi Keislaman, 2011)
This paper explores the universal principles of Islamic propagation (dakwah) according to the holy Qur?an. In doing this, the paper employs the thematic approach by collecting the Quranic verses that speak of da?wah, and interpret them analytically. Specific attention will be given to the verses that are rooted in the Arabic word da?a, which means ?to call?, and balagha, which means ?to convey?. Other verses that have to do with the activity of da?wah will be touched briefly. The paper argues that the concepts of ?calling? and ?conveying? constitute the most important and central notion of da?wah in Islam. Together the two represent the holistic Islamic idea of not only spreading out Islam, but also of building a community based on religiosity. Islamic concept of da?wah is universal because it targets not only Muslim but also all human being based on understanding, tolerance and harmony.